Effects of soy hull polysaccharide on dyslipidemia and pathoglycemia in rats induced by a high-fat-high-sucrose diet - Qian Lin; Lina Yang; Lin Han; Ziyi Wang; Mingshuo Luo; Danshi Zhu; He Liu; Xin Li; Yu Feng (Food Science and Human Wellness)
The present work aimed at investigating the effects of soy hull polysaccharide (SHP) in alleviating adverse effects in rats fed a high-fat-high-sucrose diet. After SHP feeding for 4 weeks, the fasting blood glucose (FBG), serum triglyceride (TG), serum high-density lipoprotein cholesterol (HDL-C), short chain fatty acids (SCFAs), and 16S rDNA gene sequence were determined. Administration of SHP significantly decreased body fat content and TG levels, and increased water intake and HDL-C levels after 4 weeks of treatment. The antihyperglycemic effect of SHP at a dose of 400 mg/kg mb had the most significant effects among the three dosage groups. SHP notably restored the FBG in rats fed a high-fat-high-sucrose diet (P < 0.05). Furthermore, SHP at 400 mg/kg mb increased the abundance of Bacteroidetes and decreased that of Firmicutes and Actinobacteria at the phylum level. The polysaccharide treated groups had significantly higher content of total SCFAs, and the main fermentation products were acetic, propionic, n-valeric and i-valeric acids. Thus, SHP restores blood lipid levels in rats fed a high-fat-high sucrose diet through regulation of the gut microbiota.